Clothesline Model for Total Eclipses: Shielding Like Effect of Gravity - Lalu Heriyanto (Jurnal Penelitian Pendidikan IPA, 2022)
Clothesline Model (CM) has been built. This model tries to explain the strange pattern of variations in the acceleration of Earth's gravity when a total solar eclipse or total lunar eclipse occurs. This model is built on the principle of a usual clothesline. In the CM, the concept of clothesline curvature is introduced due to an object that is hung on it and the ability of the object to reduce or affect the clothesline curvature of other objects that are also hung on the clothesline. In natural phenomena, the curvature of the clothesline in an object is interpreted as the curvature of spacetime which is a manifestation of the acceleration of gravity on the object. The influence or disturbance of an object on the clothesline curvature of another object is interpreted as the gravitational attraction of that object to another object. Based on the results of the CM analysis, the variation pattern of the earth's gravitational acceleration during a total solar eclipse is influenced by the damping factor by the moon against the disturbances from the sun and the earth. Meanwhile, the pattern of variations in the acceleration of Earth's gravity during a total lunar eclipse is influenced by the damping factor by the earth itself against disturbances from the sun and moon. From this damping effect, the moon and the earth act as gravitational shields